Combating onion fungal diseases through integrated disease management - Salunkhe, Vanita; Gawande, S J; Singh, Major (Indian Horticulture, 2019)
Onion is grown throughout three seasons, viz. kharif, late-kharif and rabi.The losses due to diseases varies with the season. On an average, fungaldiseases causes 30-50% yield losses in onions. For fungal diseasemanagement, farmers rely mainly on fungicides. Further, excessive anduntimely use of chemicals can increase the cost of production and createshealth hazards and environmental issues. This warrants an integratedapproach to manage the problem. Therefore fungal diseases and theirmanagement strategies are discussed.